(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2025)
The Belis tradition in Manggarai society represents a complex cultural practice in marriage with profound significance in social structure and interpersonal relations. This study aims to explore the philosophical dimensions of the Belis tradition through Gabriel Marcel’s conceptual perspective on Being (existence) and Having (possession). Using a qualitative approach through literature review and philosophical analysis, this research examines how the practice of Belis represents the dynamics of intersubjectivity, existential meaning, and the transformation of cultural values within the context of marriage in Manggarai society. The focus of the study is directed toward an in-depth philosophical analysis of the meaning of Being and Having in the Belis tradition, where the practice is not merely understood as a material transaction but as a medium for expressing relationships, dignity, and subjective participation among individuals. This study will reveal how the concept of possession in Belis transcends objective dimensions and embodies intersubjective values that reflect the complexity of human relationships. The findings are expected to provide a theoretical contribution to understanding the Belis cultural practice philosophically, while also offering a new perspective on interpreting marriage traditions within Manggarai society.